“Known unknowns”: reducing digital inequalities in the silver economy - José, M.; Ferreira, F.; Zopounidis, C.; Doumpos, M.; Ferreira, N. (IEEE Transactions on Engineering Management, 2024)
Because of the world’s aging population, Europe’s over-50 segment has grown significantly. This demographic trend has created a major economic opportunity known as the silver economy. Technology plays an important role in the development of products and services targeting this older market segment, yet technological innovation has compromised these individuals’ quality of life by aggravating already existing social disparities. Limited access to and use of technology is known as digital inequality, which is a matter of growing concern that is pushing experts to develop initiatives that mitigate the impact of this disparity. However, decision makers first need to be fully aware of the challenges associated with this endeavor, which arise out of the inherent complexity of digital inequality and the uncertainty produced by technological disruptions.This study addresses this decision problem by adopting a constructivist, socio-technical approach that combines cognitive mapping and decision-making trial and evaluation laboratory techniques in a neutrosophic context. Data were collected from an expert panel with experience in real-world cases. The members analyzed different strategies and their effectiveness in terms of reducing digital inequalities in the silver economy. The results were analyzed and validated by the Head of Data and Analytics at Nippon Telegraph and Telephone Data Europe and Latin America. No prior research was found that has used the same combination of operational research methods to address this decision problem. The findings include recommendations for how to facilitate the development of initiatives that increase digital literacy in a silver economy context.